Bacteroides propionicigenes sp. nov., isolated from human faeces. Issue 5 (30th May 2022) - Sun, Xin-Wei; Abdugheni, Rashidin; Huang, Hao-Jie; Wang, Yu-Jing; Jiang, Min-Zhi; Liu, Chang; Zhou, Nan; Jiang, He; Liu, Shuang-Jiang
Abstract : An anaerobic bacterial strain, designated as NSJ-90 T, was isolated from the faeces of a healthy adult in China. Cells of strain NSJ-90 T were Gram-stain-negative, non-motile, non-spore-forming and rod-shaped. Based on 16S rRNA gene sequence analysis, strain NSJ-90 T belonged to the genus Bacteroides and was phylogenetically closely related to Bacteroides clarus YIT 12056 T (16S rRNA gene identity was 97.04 %). The DNA G+C content of strain NSJ-90 T was 44.85 mol% (calculated from the genome). The average nucleotide identity between strain NSJ-90 T and B. clarus YIT 12056 T was 87.60 %. The major cellular fatty acids (>10 %) of strain NSJ-90 T were iso-C15 : 0, anteiso-C15 : 0 and iso-C17 : 0 3-OH. Menaquinone-10 was detected as the respiratory quinone. The major products of glucose fermentation were acetic, propionic and isovaleric acids. Based on its phylogenetic, phenotypic and chemotaxonomic characteristics, we propose that strain NSJ-90 T represents a novel species of the genus Bacteroides, for which the name Bacteroides propionicigenes sp. nov. is proposed. The type strain is NSJ-90 T (=CGMCC 1.17886 T =KCTC 25305 T ).